Penerapan Model Pembelajaran Kontekstual Pada Mata Pelajaran PAI Kelas V Di Madrasah Ibtidaiyah Negeri 2 Lebong - Gondo, Baherwan; Siswanto; Fransiska, Jeni (Al-Mau'izhoh: Jurnal Pendidikan Agama Islam, 2025)
The writing of this scientific work aims to determine the application of contextual learning models in PAI class V subjects at MIN 2 Lebong. This research uses a qualitative descriptive method to describe the conditions that occur in the field. The object of research includes students, educators, and parents, with primary and secondary data as sources of information. Data collection techniques include observation, interviews, and documentation, while data analysis is done through reduction, presentation, verification, and conclusion drawing. The results showed that the application of contextual learning models made it easier for students to understand the material and relate it to everyday life. Teachers play an active role in encouraging direct student involvement so that they can find knowledge through experience. The implementation has gone well but not maximized. Supporting factors include good teacher-student relationships and supportive classroom conditions although sometimes noisy. Meanwhile, barriers to implementation include low student interest in learning, significant differences in intelligence, and student behavior that does not always receive the material well. However, teachers continue to try to overcome these obstacles through interesting approaches and continuous understanding.